Hybrid SiO2@POSS nanofiller: a promising reinforcing system for rubber nanocomposites. (17th March 2017) - D'Arienzo, Massimiliano; Redaelli, Matteo; Callone, Emanuela; Conzatti, Lucia; Di Credico, Barbara; Dirè, Sandra; Giannini, Luca; Polizzi, Stefano; Schizzi, Ilaria; Scotti, Roberto; Tadiello, Luciano; Morazzoni, Franca
Abstract : Hybrid SiO2 @POSS provides enhanced networking and "sticky regions" among filler aggregates, granting outstanding reinforcement and hysteretic properties to SBR nanocomposites. Abstract : A novel hybrid nanofiller, SiO2 @POSS, where the silica nanoparticles (NPs) and the POSS belong to the same functional structure, has been synthesized by grafting different loadings of OctaMethacrylPOSS onto silanized commercial SiO2, using a surface reaction mediated by dicumylperoxide (DCP). The peroxide, besides anchoring the nanocages onto the silica surface, ensures the presence of methacryl functionalities in the final structure, which are still available for cross-linking reactions with a polymer host. The hybrid SiO2 @POSS NPs were used to prepare, by ex situ blending, SBR nanocomposites. The dynamic-mechanical analysis performed on the cured SBR/SiO2 @POSS composites indicated that the presence of POSS induces a remarkable increase of modulus either at low or at high strain, and a considerable decrease of hysteresis. This has been associated with the peculiar hybrid structure of the SiO2 @POSS filler, in which silica NP aggregates are partially interconnected and surrounded by a thin shell of POSS nanounits which, thanks to their high number of reactive functionalities, promote the formation of "sticky regions" among the silica aggregates and, consequently, a tight filler network wherein rubber is immobilized. This grants a relevant reinforcement and increased hysteretic properties, suggesting SiO2 @POSS as a promising filler system for decreasing the energy loss under strain and for leading to a potential reduction of filler utilization in rubber composite formulations.